+0  
 
0
53
1
avatar

Solve for the variable x in terms of y and z, assuming y \neq \frac{1}{2}:
xy + x = \frac{3x + 2y + z + y + 2z}{3}

 Jul 21, 2023
 #1
avatar+14964 
+1

Hello Guest!

 

\(xy + x = \dfrac{3x + 2y + z + y + 2z}{3}\ |\cdot 3\\ 3xy + 3x = 3x + 2y + z + y + 2z\ | -3x\\ 3xy= 2y + z + y + 2z\ |\ \div (3y)\\ x=\dfrac{2}{3}+\dfrac{z}{3y}+\dfrac{1}{3}+\dfrac{2z}{3y}\ |\ add\ and\ reduce\\ \color{blue}x=\dfrac{z}{y}+1\)

laugh  !

 Jul 21, 2023
edited by asinus  Jul 21, 2023
edited by asinus  Jul 21, 2023

4 Online Users

avatar
avatar
avatar